Direct Comparison of Demyelinating Disease Induced by the Daniel's Strain and BeAn Strain of Theiler's Murine Encephalomyelitis Virus - Zoecklein, Laurie J. (Brain Pathol, 2006)
We compared CNS disease following intracere‐bral injection of SJL mice with Daniel's (DA) and BeAn 8386 (BeAn) strains of Theiler's murine encephalomyelitis virus (TMEV). In tissue culture, DA was more virulent then BeAn. There was a higher incidence of demyelination in the spinal cords of SJL/J mice infected with DA as compared to BeAn. However, the extent of demyelination was similar between virus strains when comparing those mice that developed demyelination. Even though BeAn infection resulted in lower incidence of demyelination in the spinal cord, these mice showed significant brain disease similar to that observed with DA. There was approximately 100 times more virus specific RNA in the CNS of DA infected mice as compared to BeAn infected mice. This was reflected by more virus antigen positive cells (macrophages/microglia and oligodendrocytes) in the spinal cord white matter of DA infected mice as compared to BeAn. There was no difference in the brain infiltrating immune cells of DA or BeAn infected mice. However, BeAn infected mice showed higher titers of TMEV specific antibody. Functional deficits as measured by Rotarod were more severe in DA infected versus BeAn infected mice. These findings indicate that the diseases induced by DA or BeAn are distinct.